Towards gender-informed adaptation planning in the Sudanian zone of Mali Analysis of climate change vulnerability - Magassa, Mariame; Partey, Samuel T.; Houessionon, Prosper; Dembélé, Siaka; Ouédraogo, Mathieu; Zougmoré, Robert B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Understanding the linkages between gender and vulnerability is crucial for proposing sustainable gender-responsive climate-smart solutions. This study compared the vulnerabilities of male (MHHH) and female household heads (FHHH) in the Sudanian zone of Mali using Cinzana in the Segou region as a case study. We used semi-structured questionnaire interviews and focus group discussions for data collection. The questionnaires were randomly administered to 233 household heads (23% women). The Livelihood Vulnerability Index (LVI) method was used to assess vulnerability to climate change. The results showed that livelihoods in the Sudanian zone of Mali are vulnerable to climate change. Female household heads (FHHH) were found to be more vulnerable. FHHH recorded higher values for six out of the eight LVI major components used in the vulnerability assessment: socio-demographic index, livelihood strategies index, social network index, food index, natural disasters and climate variability index and agricultural production system index. The study proposes a number of interventions for improving the adaptive capacity of FHHH to climate change and variability: improving access to financial resources, improving access to radio for receiving weather information, encouraging FHHHs involvement in farmer-based groups for peer-learning; and promoting the development of policy initiatives that ensure the mainstreaming of gender into agricultural development programs.